A STUDY ON THE ROLE OF ENTREPRENEURSHIP EDUCATION IN PREPARING MILLENNIALS FOR GLOBAL ECONOMIC CHALLENGES - Said Ahmad, Muh. Ihsan (Technopreneurship and Educational Development Review (TENDER), 2024)
This study aims to explore the role of entrepreneurship education in preparing millennials to face global economic challenges. Using a literature review method and a qualitative approach, a descriptive analysis was conducted on 20 scientific articles selected from an initial 38 articles retrieved via Google Scholar for the period 2015–2024. The findings indicate that entrepreneurship education significantly enhances millennials' innovation skills, digital technology mastery, and risk-taking abilities. Case studies such as Tokopedia, Aruna, and Sayurbox highlight the importance of collaboration between educational institutions, the government, and industries to support the development of young entrepreneurs capable of competing in the global market. However, challenges such as curriculum limitations, the quality of educators, and access to financing remain obstacles. This study provides essential implications for designing more innovative and strategic entrepreneurship curricula and recommends cross-sector collaboration as a key factor for successful entrepreneurship education.